Heir of the Prophets: Veneration of Ḥusayn b. ‘Alī and the Socio-Religious Positioning of Twelver Shiism - Qazwini, Hadi (Islamic Studies, 2021)
This article explores veneration of Ḥusayn b. ‘Alī (d. 61/680) and the place of his ritual visitation (ziyārah) and pilgrimage to his tomb in Karbala in the construction of Twelver Shī‘ī socio-religious identity. Following the theoretical approach of social identity theory, I argue that Twelver Shī‘ī veneration of Ḥusayn operates not only vertically, that is, to appeal to the divine, but also horizontally, that is, to secure a prominent socio-religious lineage for Twelver Shī‘īs vis-à-vis the non-Shī‘ī Muslim, Jewish, and Christian traditions. Through close reading and analysis of reports (ḥadīths/akhbār) compiled by Ibn Qūluwayh (d. 368-9/978-9) in his Kāmil al-Ziyārāt (The Complete Visitations), a fourth/tenth- century text devoted entirely to the theme of ritual pilgrimage, I conceptualize three levels of Twelver Shī‘ī socio-religious positioning. First, reports in this text encourage veneration of Ḥusayn and pilgrimage to his tomb as an indispensable feature of individual and communal Twelver Shī‘ī identity. Second, reports express veneration of Ḥusayn and his burial site as a marker of rivalry vis-à-vis the non-Shī‘ī Muslim tradition. Finally, the socio-religious place of Twelver Shī‘īs is further enhanced through reports depicting major figures from the Jewish and Christian traditions as participating in the veneration of Ḥusayn.